Light-Emitting Diodes: Research, Manufacturing, and Applications XI 2007
DOI: 10.1117/12.701301
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental mechanisms of electroluminescence refrigeration in heterostructure light-emitting diodes

Abstract: The fundamental mechanisms of electroluminescence (EL) refrigeration in heterostructure light emitting diodes, is examined via carrier energy loss (and gain) during transport, relaxation, and recombination, where the contribution of electrons and holes are treated separately. This analysis shows that the EL refrigeration process is a combination of thermoelectric cooling that mainly occurs near the metal/semiconductor contacts and radiative recombination which mainly occurs in the active region. In semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…In 1959 a US Patent was granted for a refrigeration device based on the principle [24]. In the last decade, the applied literature on the subject has expanded to include more realistic modeling and more recent advances in device fabrication technologies [1,2,3,4,5,6,7] and at least one attempt to demonstrate practical cooling is currently underway [8]. Nevertheless, prior to this work, the basic phenomenon of electrically-driven light emission above unity efficiency had never been experimentally verified.…”
Section: Previous Work Toward Unity Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1959 a US Patent was granted for a refrigeration device based on the principle [24]. In the last decade, the applied literature on the subject has expanded to include more realistic modeling and more recent advances in device fabrication technologies [1,2,3,4,5,6,7] and at least one attempt to demonstrate practical cooling is currently underway [8]. Nevertheless, prior to this work, the basic phenomenon of electrically-driven light emission above unity efficiency had never been experimentally verified.…”
Section: Previous Work Toward Unity Efficiencymentioning
confidence: 99%
“…It has long been known that in theory a light-emitting diode (LED) may emit optical power in excess of the electrical power required to drive it, with the remainder drawn from lattice heat. This phenomenon has been referred to in the literature by various authors as electro-luminescent cooling [1,2], electroluminescence refrigeration [3,4], opto-thermionic cooling [5,6], the operation of a "Thermischer Konverter" [7], and thermo-photonic cooling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical results from the past few years have suggested that modern epitaxial growth and fabrication methods may enable practical devices for thermal energy conversion [6], [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the work of the author and his direct collaborators, two recent experimental e↵orts have been documented, one at Arizona State University and the other at Aalto University in Finland. In parallel with basic theoretical work on the role of heterostructures [14] and low-dimensional systems [15] in the phenomenon, the group at Arizona State fabricated a microstructure [16,17] designed to produce a 6 C drop due to electro-luminescent cooling. Although the group's publications indicate that a substantial experimental e↵ort was made to realize cooling, net cooling has not been reported as of yet.…”
Section: Introductionmentioning
confidence: 99%